A preservação audiovisual na América Latina - Cuarterolo, Andrea; Nagime, Mateus (Imagofagia, 2021)
Introdução ao dossiê " A preservação audiovisual na América Latina" Resumen: Introducción al dossier "La preservación audiovisual en América Latina" Abstract: Introduction to the dossier "The Audiovisual Preservation in Latin America”